Я познаю мир. Экология: энциклопедия / [авт.-сост. А.Е.Чижевский] - Чижевский А.Е. (АСТ; Астрель, 2008)
Экземпляры: ф.5,12 (24.12.2008) / Инвентарный номер: 40797 / Цена: 80.90 / Авт.знак: Я 11 / ББК: 20.1я2